Class S: appropriation of ‘lesbian’ subculture in modern Japanese literature and New Wave cinema - Shamoon, Deborah (Cultural Studies, 2021)
In the 1920s in Japan, girls attending single-sex secondary schools developed a girls’ culture (shōjo bunka) or subculture to insulate themselves temporarily from the pressures of patriarchal society. Part of this subculture was a practice called s kankei (s or sister relationships), also called Class S, which were same-sex romantic attachments between classmates, condoned at the time as a temporary practice relationship that would end upon graduation, followed by an arranged marriage. Although s relationships were not ‘lesbian’ in the contemporary sense, literature and film created by men in the 1920s through the 1960s appropriated aspects of girls’ culture, including exploitative representation of female homosexuality. One example is Manji (Quicksand, 1928) by Tanizaki Jun’ichirō, which depicts an s relationship as lurid and perverse. Kawabata Yasunari plagiarized from his female disciple Nakazato Tsuneko in order to publish the most popular Class S novel of the era, Otome no minato (Harbor of Girls, 1937). Kawabata also included exploitative scenes of female homosexuality in his novel Utsukushisa to kanashimi to (Beauty and Sadness, 1963). Both Tanizaki’s and Kawabata’s novels were made into films by New Wave directors, Manji in 1964 by Masumura Yasuzō and Beauty and Sadness in 1965 by Shinoda Masahiro, and featured the first depictions of ‘lesbianism’ in Japanese film. Although these films reinscribe the male gaze, they helped inspire a nascent gay culture and opened the way for more authentic gay cinema. This essay recenters girls’ culture in modern Japanese literature and film, and discusses the variable meaning of female homosexuality for different audiences.
Keywords: approches et analyses; arts; asie; discipline; discours dominant; japon; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; systèmes d'oppressions; études culturelles; études littéraires

Sémi: roman - Shimazaki, Aki (Actes Sud, 2021)
« Après plus de quarante ans de mariage, Tetsuo et Fujiko se sont installés en maison de retraite car Fujiko, atteinte de la maladie d’Alzheimer, requiert une prise en charge particulière. Un matin, au réveil, elle ne reconnaît plus son époux. D’abord en grand désarroi, Tetsuo entreprend finalement de reconquérir celle qui le prend désormais pour un étranger auquel elle se trouve simplement fiancée. »– Site de l'éditeur
Section: 150 pages ; 19 cm.
Keywords: arts; asie; care; cours; discipline; japon; lit2815; premier cycle; roman; régions géographiques; thématiques; écriture des femmes*; études littéraires

Masculinity, race and national identity: representations of non-Japanese men’s speech in contemporary Japanese novels - Suzuki, Satoko (Gender and Language, 2020)
Language ideologies have been of central concern to the study of Japanese language, gender and society. Many scholars have researched ideologies surrounding representations of Japanese women’s speech; however, investigations of representations of men’s speech have been limited. This study contributes to filling this gap through the analysis of non-Japanese male characters found in contemporary Japanese novels. The article reveals that authors assign strongly masculine expressions to their East Asian characters much more frequently than to their white characters and argues that these differentiated representations of non-Japanese male characters’ speech reproduce and are influenced by ideologies concerning cultural nationalism, racial determinism, class and sexuality. Linguistic data are presented that both unsettle the constructed image of Asian males as asexual beings and question the historically assumed relationship between gendered language and authenticity.
Keywords: arts; asie; cours; discipline; histoire et politique; japon; lin2685; linguistique; masculinité; premier cycle; représentation des hommes; régions géographiques; sciences humaines; sofia; thématiques; études littéraires

Queer China: Lesbian and gay literature and visual culture under postsocialism - Bao, Hongwei (Routledge, Taylor & Francis Group, 2020)
Ce livre analyse la production culturelle queer dans la Chine contemporaine pour cartographier les vastes transformations sociales en matière de genre, de sexualité et de désir. Il examine la littérature queer et les cultures visuelles de l'ère post-Mao et postsocialiste de la Chine pour montrer comment ces diverses formes et pratiques culturelles fonctionnent non seulement comme des formes d'activisme social spécifiques au contexte et culturellement sensibles, mais produisent également des types distincts de subjectivités de genre et sexuelles propres à Les conditions postsocialistes de la Chine. De la poésie à l'art du découpage de papier, de la « littérature camarade/gay » aux fanfictions amoureuses entre filles, des films lesbiens aux documentaires activistes, et d'un spectacle de dragsters à Shanghai à une représentation publique d'un mariage homosexuel à Pékin, le livre révèle une Chine queer dans toute sa complexité idéologique et son énergie créatrice. Riche empiriquement et méthodologiquement éclectique, Queer China tisse habilement la recherche historique et archivistique, l'analyse textuelle et discursive, ainsi que les entretiens et l'ethnographie. Innovant et mettant en avant une perspective non occidentale, ce travail transdisciplinaire contribue à de multiples domaines académiques, notamment les études littéraires et culturelles, les études sur les médias et la communication, les études cinématographiques et cinématographiques, l'art contemporain, les études de théâtre et de performance, les études de genre et de sexualité. , études Chine/Asie et pays du Sud, histoire culturelle et géographie culturelle, théorie politique et étude des mouvements sociaux.
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; chine; cinéma; communication; discipline; queer; régions géographiques